Transpressive Deformation in the Southern European Variscan Belt: New Insights From the Aiguilles Rouges Massif (Western Alps). Issue 6 (11th June 2020) - Simonetti, M.; Carosi, R.; Montomoli, C.; Cottle, J. M.; Law, R. D.
Abstract: Despite the Mediterranean sector of the Variscan Belt being fragmented and reworked during Alpine orogenesis, evidence for the activity of a right‐lateral strike‐slip shear zone has been reported in Paleozoic fragments of the belt such as the Sardinian Variscan Basement, the Maures Massif of southern France, and in the Western Alps. To improve this correlation with new structural data, we performed a structural and microstructural analysis incorporating study of the kinematics of flow and petrochronology of a high‐strain zone in the Aiguilles Rouges Massif (External Crystalline Massifs, Western Alps). The results higlight a dextral pure‐shear dominated transpression initiated under amphibolite‐facies metamorphic conditions (~630°C, 0.4 GPa) during Variscan time. The structural evolution of the high‐strain zone is similar to the Ferriere‐Mollières shear zone in the Argentera Massif; both are transpressive shear zones active at the same time (~320 Ma) under similar metamorphic conditions. These two high‐strain zones represent well‐preserved segments of a system of ductile shear zones in the External Crystalline Massifs. The data presented in this study provide improved constraints on the extent, kinematics, and timing of the East Variscan Shear Zone in the Variscan basement of the Western Alps, with implications for refining the correlation between structures in fragments of the southern Variscan Belt. The data also better constrain a segment of a major pre‐Alpine shear zone which may have played an important role during post‐Variscan tectonics as an inherited discontinuity. Key Points: The Aiguilles Rouges Massif underwent transpression at ~320 Ma similarly to Argentera Massif, Maures Massif, and Corsica‐Sardinia Block Aiguilles Rouges Massif, Argentera Massif, Maures Massif, and Corsica‐Sardinia Block were all part of the East Variscan Shear Zone The East Variscan Shear Zone is a long‐lasting system of shear zones that evolved following the "growth by linkage" model